Δ15N and nutrient stoichiometry of water, aquatic organisms and environmental implications in Taihu lake, China. (June 2018) - Tao, Yu; Dan, Dai; Kun, Lei; Chengda, He; Haibing, Cong; Guo, Fu; Qiujin, Xu; Fuhong, Sun; Fengchang, Wu
Abstract: Nitrogen pollution has become a worldwide problem and the source identification is important for the development of pertinent control measures. In this study, isotope end members (rain, nitrogen fertilizer, untreated/treated sewage), and samples (river water discharging to Taihu lake, lake water, aquatic organisms of different trophic levels) were taken during 2010–2015 to examine their δ 15 N values and nutrient stoichiometry. Results indicated that phytoplankton (primary producers), which directly take up and incorporate N from the lake water, had a similar δ 15 N value (14.1‰ ± 3.2) to the end member of treated sewage (14.0‰ ± 7.5), and the most frequently observed δ 15 N value in the lake water was 8–12‰, both indicating the dominant impact of the sewage discharge. Relationship analysis between N isotope value of nitrate and nitrate concentration indicated that different N cycling existed between the algae-dominated northwest lake (NW) and the macrophyte-dominated southeast lake (SE), which is a result of both impacts of river inputs and denitrification. Our nutrient stoichiometry analysis showed that the lake water had a significantly higher N:P ratio than that of algae (p < 0.05), suggesting that N is available in excess relative to the amount demanded by the algae. The long-term trend of the socio-economic development in the watershed further confirmed that the rapid population increase and urbanization have resulted in a great change in the N loading and source proportion. We suggest that although P control is necessary in terms of eutrophication control, N pollution control is urgent for the water quality and ecological recovery for Taihu lake. Graphical abstract: Image 1 Highlights: δ 15 N of end members and river, lake water, and aquatic organisms were characterized. Nutrient stoichiometry was analyzed and contrasted for lake water and phytoplankton. N isotopic analysis indicates that domestic sewage is the dominant N contributor. Rapid urbanization has led to shift of major N source and load proportion in the basin.